2010
DOI: 10.1007/s13355-010-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect of proteins derived from Xestia c-nigrum granulovirus on Mamestra brassicae nucleopolyhedrovirus infection in larvae of Autographa nigrisigna (Lepidoptera: Noctuidae) on cabbage

Abstract: The insecticidal effect of Mamestra brassicae nucleopolyhedrovirus (MabrNPV) and the enhancing activity of proteins derived from occlusion bodies (OBs) of Xestia c-nigrum granulovirus (GVPs) on the infectivity of MabrNPV were evaluated in a bioassay with second-instar larvae of Autographa nigrisigna (Walker) fed virus-applied cabbage plants. The lethal concentrations of MabrNPV achieving 50 and 95% mortality for A. nigrisigna were estimated to be 1.4 9 10 5 and 3.1 9 10 6 OBs/ml, respectively. When larvae were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The use of mixtures containing granulovirus and nucleopolyhedrovirus has been studied in order to observe a synergic effect in the co-infections and in some cases granuloviruses are able to enhance the infectivity and virulence of NPVs [ 15 , 16 ]. This could be used as strategy for development of a biopesticide to control the FAW in maize crop in America.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mixtures containing granulovirus and nucleopolyhedrovirus has been studied in order to observe a synergic effect in the co-infections and in some cases granuloviruses are able to enhance the infectivity and virulence of NPVs [ 15 , 16 ]. This could be used as strategy for development of a biopesticide to control the FAW in maize crop in America.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the first trial, the addition of GVPs significantly reduced the LT 50 of NPV infected larvae ( Table 4 ). Our previous bioassays using the second instar larvae of M. brassicae [ 38 ], H. armigera [ 39 , 40 ] and A. nigrisigna [ 41 ] indicated the effect of GVPs not only increases the infectivity of MabrNPV but also shortens the lethal time and/or causes death at a younger instar. These trials in 2008 verified the desirable effects of GVPs on MabrNPV infection in the cabbage field.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study confirmed that XecnGV had proteins with potency to improve the efficiency of NPV in their capsules [ 38 ]. Our detailed bioassays using an artificial diet or cabbage seedling revealed that a combination of MabrNPV with proteins derived from XecnGV capsules (GVPs) improves the insecticidal activity of MabrNPV against not only M. brassicae but also H. armigera and Autographa nigrisigna [ 38 , 39 , 40 , 41 ], suggesting prospects for a new biological insecticide against three important noctuid pests of cruciferous crops. Since the insecticidal activity and persistence of viruses in the field are affected by environmental factors—for example sunlight, rainfall, and temperature—as well as biotic factors such as density and age structure of the pest population, field studies would be necessary to evaluate the efficacy of the combined formulation of MabrNPV with GVPs on the control of these noctuid pests.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have employed NPVs with extracts of GV OBs, as the proteins possessing enhancing activity do not need further purification. GVP obtained from XcenGV were successfully used as additives for MbMNPV on Mamestra brassicae , Helicoverpa armigera , and Autographa nigrisigna larvae [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Baculovirus Interactions In Vivomentioning
confidence: 99%